Governing the countryside through state-led programmes: A case study of Jiangning District in Nanjing, China. (May 2018) - Shen, Mingrui; Shen, Jianfa
Over the last decade, a large part of the Chinese countryside has experienced a 'hollowing out' process in economy and state administration, as rapid urbanisation and development have concentrated in urban areas. To deal with this challenge, the Chinese government has launched rural programmes, resulting in significant transformation in the countryside. Applying the state rescaling theory as an analytical lens, this paper argues that these state-led rural programmes have strengthened the state role in governing the countryside significantly based on the case study of Jiangning. These programmes are not fixed yet developed and expanded through the interaction of multi-level governments. While local governments follow the discourse of the higher-level governments in this process, they also restructure the state apparatus for programme implementation. Local governments have some autonomy by echoing and responding to the initiative of the higher-level governments actively. Thus the programme evolution is not simply a top-down process as it encompasses interesting dynamics of state rescaling. Generally speaking, the state plays an important role in moving toward 'good governance' in rural China at the initial stage. The state-led rural programmes enable the state to regain its leading role in the countryside and restore the rural public administation to some extent. There is still a long way to go for the civil society to achieve self-governance in the countryside.